Recent Clinical Trials and Industry Updates on EGFR Inhibitors (2024-2025) - Magar, Vidya Kishanrao; Khavane, Karna Bhagwanrao (Indian Journal of Pharmacy Practice)
The Epidermal Growth Factor Receptor (EGFR) signaling pathway has been and still is essential in the genesis and therapy of several solid tumors, the most famous among them being Non-Small Cell Lung Cancer (NSCLC) and Metastatic Colorectal Cancer (mCRC). Major changes in clinical practice and regulatory approvals have been made as a result of the recent progress from 2024 till 2025. In NSCLC, the LAURA trial showed the advantage of osimertinib as consolidation therapy after chemoradiation in unresectable stage III disease, whereas the FLAURA2 trial confirmed that the combination of osimertinib and chemotherapy was more effective as first-line metastatic setting, thus the indication was extended. The MARIPOSA study gave the green light to the combination of amivantamab with lazertinib as a new first-line treatment, and the PAPILLON study supported the employment of amivantamab in combination with platinum-pemetrexed for the tumors carrying the EGFR exon 20 insertion mutation. Furthermore, sunvozertinib was granted accelerated approval for the treatment of patients with exon 20 insertion-positive NSCLC who had undergone prior therapy, and some newly-developed fourth-generation EGFR inhibitors, like the ones targeting resistance C797S, are already in the process of being further developed. On the other hand, mCRC progressed in parallel with the unveiling of updated results of the PARADIGM trial that demonstrated the effectiveness of anti-EGFR antibodies in RAS wild-type left-sided tumors and with data from prospective studies showing the practicality of ctDNA-guided rechallenge in later-line settings. Altogether, these developments highlight the fact that precision medicine is continuously optimizing EGFR-targeted therapies in various cancer types, thus, not only are patients being presented with new treatment options and doses of hope but also coming possibilities of drug discovery are being informed.
Keywords: Osimertinib; FLAURA2 Trial; LAURA Trial; Amivantamab; Lazertinib; MARIPOSA Trial; PAPILLON Trial